PENGARUH LEVERAGE, GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN - Nabila Y. Ahmad; Rusman Soleman; Mahardika Catur Putriwana Malik; Kasim Sinen (Nusantara Hasana Journal, 2025)
The objective of this research is to investigate the impact of leverage, board of direcots, board of commissioners, institutional ownership, capital structure, and liquidity on profitability. The data utilized in this study comprises secondary data derived from the annual reports of mining firms listed on the Indonesian Stock Exchange from 2019 to 2023. The sample was selected using purposive sampling technique, resulting in a total of 20 companies inclueded in the sample. Multiple linear regression analysis was employed as the analytical model in this research. The findings indicate that the board of directors has positive effect on profitability. Capital structure has negative effect on profitability. While leverage, board of commissioners, institutional ownership, and liquidity have no effect on profitability.